2013
DOI: 10.1097/jom.0b013e31829c76b3
|View full text |Cite
|
Sign up to set email alerts
|

Construction Workers Struggle With a High Prevalence of Mental Distress, and This Is Associated With Their Pain and Injuries

Abstract: Objectives We aimed to investigate how mental distress was associated with pain and injuries in a convenience sample of construction workers. Methods A cross-sectional, mental health assessment was conducted in a convenience sample of construction workers (N=172). A subsample participated in a clinical interview (N=10). We used a cut-off (≥1.50) on HSCL-25 to determine substantial mental distress and determined associations with pain and injury outcomes. Results The prevalence of substantial mental distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 39 publications
7
64
1
Order By: Relevance
“…This may explain why construction workers were more likely to receive prescription opioids post-injury than workers in other industries. 20 Furthermore, studies suggest that injury and chronic pain could lead to poor physical and mental health [35][36][37] ; and poor physical and mental health were associated with greater prescription opioid use, which was supported by this study and previous research. 38,39 T A B L E 1 Demographics and prevalence of prescription opioid use among construction workers, 2011-2017 (average)…”
Section: Resultssupporting
confidence: 77%
“…This may explain why construction workers were more likely to receive prescription opioids post-injury than workers in other industries. 20 Furthermore, studies suggest that injury and chronic pain could lead to poor physical and mental health [35][36][37] ; and poor physical and mental health were associated with greater prescription opioid use, which was supported by this study and previous research. 38,39 T A B L E 1 Demographics and prevalence of prescription opioid use among construction workers, 2011-2017 (average)…”
Section: Resultssupporting
confidence: 77%
“…In Massachusetts, in 2015, according to data reported by employers to the Bureau of Labor Statistics, four out of every 100 construction workers were injured on the job, with half of these injuries resulting in time lost from work. In a recent Massachusetts study of construction workers on a large commercial construction site, 74% reported having some kind of musculoskeletal pain in the last 3 months and about 40% reported having one or more injuries in the last month . This study also found high rates of mental distress and lack of treatment, and the authors hypothesized that “stigmatization and fear of job loss may interfere with help‐seeking behaviors.” In interviews conducted by the Mystic Valley Public Health Commission, construction workers discussed the pressure to work in pain and the common use of opioids, both prescribed and those obtained without a prescription, to maintain employment .…”
Section: Discussionmentioning
confidence: 91%
“…Some sources of psychological disorders cannot be avoided such as the death of a loved one, illness, company or national problem [31]. It is better to accept these situations instead of railing over things that cannot be changed, even though it may seem difficult but will be easier over time [4] [14]. Accepting the cause involves positive reappraisal, which are efforts to derive positive meanings from inevitable causes such as work-related challenges [29] [38].…”
Section: Accept the Cause Cannot Be Changedmentioning
confidence: 99%
“…Previous studies have shown that construction personnel could be exposed to various forms of psychological health risk factors, which lead to various psychological health conditions such as burnout, workaholism, stress, anxiety or depression [1] [2]. For instance, the demanding, uncertain and dynamic nature of the construction industry could expose construction employees to occupational psychological disorders [3] [4]. Psychological disorders or health conditions of construction personnel usually emanate from construction work-related factors, personality characterizes, and individual lifestyles [5] [6].…”
Section: Introductionmentioning
confidence: 99%